Inclusively walkable: exploring the equity of walkable housing in the San Francisco Bay Area. Issue 5 (3rd May 2016) - Riggs, William
Abstract : This study evaluates the inclusiveness of walkable housing in the San Francisco Bay Area. Using a series of regression models that control for an array of factors, this study finds that blacks are more likely to live in less walkable areas, a factor which could result in increased societal costs. These models suggest that this factor may mask other highly collinear factors including income, education, and social networks. This phenomenon is explored with qualitative interviews that reinforce this finding and illustrate the many push and pull factors that influence housing choice. These findings are then used to develop potential hypotheses as to why minorities may be living in less walkable locations and to propose policy solutions that could be used to encourage more inclusive walkable housing.